Leveraging Social Media Networks' Impact on Technopreneurship - Isa, Khairunesa; Palpanadan, Sarala Thulasi; Saparudin , Intan Farhana; Zainol, Nur Zainatul Nadra; Syahrudin (International Journal of Advanced Science Computing and Engineering, 2024)
Technology has become an integral part of society, substantially contributing to its many facets. With the advent of technology, media entrepreneurship in Malaysia has expanded significantly. The younger generation, specifically Generation Z, relies heavily on social media for communication, information inquiry, and online purchasing and selling. This change has had a significant impact on the Malaysian field of technopreneurship. Therefore, the purpose of this study is to examine the relationship between the factors that influence Generation Z's use of social media for business and their propensity to engage in technopreneurship. This quantitative study utilizes a questionnaire to gather demographic information, explore factors influencing Generation Z's use of social media for business purposes, and examine their motivations and aspirations for engaging in technopreneurship activities. 280 respondents from Generation Z technopreneurs were selected through random sampling. The software Statistical Package for the Social Sciences (SPSS) was used to perform a descriptive analysis of the obtained data. According to the study's findings, each factor has a significant relationship with the motivation to engage in technopreneurship. By adopting these strategies, the government can help new and aspiring entrepreneurs make better-informed choices and utilize technology effectively to expand their businesses. This can boost the digital economy and generate new jobs in the tech industry. Consequently, policymakers and stakeholders should consider the study's findings and take proactive steps to promote technopreneurship development in Malaysia.